The perceptions of newly qualified nurses on the guidance by preceptors towards becoming experts in nursing - Warriodene Hansen (AOSIS, 2021)
Background: The new role as professional nurse can be a difficult transition for the new qualified nurses. During this time, factors such as not being well prepared, working without supervision and a lack of guidance can be the result of a difficult transition. Objectives: The purpose of this study is to assess the perceptions of newly qualified nurses on the guidance given by their preceptors towards becoming experts in practice at a Level II regional hospital in the Western Cape. Method: A non-experimental quantitative descriptive design was followed. Collection of data was done by means of a questionnaire, designed by the researcher, using a cross-sectional research method. Non-probability sampling produced a sample of 162 nurses comprising registered nurses (48.2%), enrolled nurses (32.7%), and enrolled nursing auxiliaries (19.1%). Statistical analysis was performed using the Statistical Analysis System (SAS), version 9.3. Results: The results of the research study indicated that respondents had more positive experiences than negative ones. The respondents indicated that for the role and characteristics of the preceptor, expectations were met for knowledgeability, professionalism and contribution to team work. Furthermore, the results indicated that the respondents would recommend preceptorship. Conclusion: Preceptorship is one of the major interventions available to support newly qualified nurses by easing the transition from student to practicing nurse and reducing the theory-practice gap. The findings emphasised the importance of ongoing support programmes for nurses after obtaining a new qualification or/and being a new nurse.